Adolescentes usuários de substâncias psicoativas: desafios vivenciados em internações psiquiátricas e as possibilidades de cuidado no CAPSad - Pereira, Natalia Alonso (Universidade Federal de São Carlos, 2022)
The literature has shown that the adherence of adolescents users of Psychoactive Substances (PAS) is still a challenge, and alerts us to the need to consider the specific aspects of this period. Thus, the aim of this study was to understand the perceptions of adolescents who use PAS about their experiences in psychiatric hospitalizations and follow-ups received in the Centers for Psychosocial Care Alcohol and Drugs (CPSCad) as well as identify the challenges and benefits experienced in these occasions. This is an exploratory and qualitative study. Four adolescentes, linked to two CPSCad from two cities in the interior of São Paulo state, who had a history of psychiatric hospitalization and who answered a semi-structured interview, participated in the study. The interviews were transcribed and analyzed by the Content Analysis method. These adolescents started using drugs early, have experiences of "heavy" drugs uses and come from social vulnerability contexts. The hospitalization were involuntary, and aspects such as family distancing, feeling of confinement, situations of lack of security and as well as the absence of diversified approaches in daily life were considered the greatest challenges experienced in them. It was identified that the understanding that they would have served their sentence through this isolation, detoxification, the recognition of the need for help and the damages associated with the consumption of PAS were the main contributions of psychiatric hospitalizations. Regarding the treatment offered by CPSCad, there was greater acceptance when compared to hospitalizations. The difficulty of abstinence, and displeasure with some activities and with the approaches during the care attendance were the greatest challenges experienced in the service, as for their contributions, they consider it and acquisition of socioemotional skills. It is argued that hospitalization remains strongly characterized as punishment, isolation and control, and that only referrals, both for hospitalization and for post discharge, are configured as communication between the care devices where the study was conducted. Regarding CPSCad, the need for review and expansion of care actions in the territory is pointed out, in a network and articulated with the demands of adolescents and their families, prioritizing the protagonism of adolescents in the process of their care.
Adolescents users psychoactive substances: challenges experienced in psychiatric hospitalizations and the possibilities of care in CAPSad
Keywords: Hospitais psiquiátricos; CAPSad; Adolescência; Transtornos relacionados ao uso de substâncias; Terapia Ocupacional; Psychiatric Hospitals; Adolescence; Substance use disorders; Occupational Therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL